(untitled) (Canadian Dermatology Today, 2023)
The world of device-based treatments of the skin is unregulated, with minimal enforcement of laser operator training and credentials, combined with an often purposeful “gray zone” in terms of qualifications communicated to patients. Dermatologists and the staff they directly supervise are at an advantage when it comes to appropriately diagnosing conditions of the skin, as well as delivering effective and safe treatments. Light- and laser-based devices are one of the many tools in the dermatologist’s armamentarium and optimizing their use has the potential to provide superior outcomes for patients. We share herein pearls from nearly ten years of experience in the field to refine your laser dermatology practice.